Perceived facilitators and barriers to chronic disease management in primary care networks of Singapore: a qualitative study. Issue 5 (4th May 2021) - Foo, Chuan De; Surendran, Shilpa; Tam, Chen Hee; Ho, Elaine; Matchar, David Bruce; Car, Josip; Koh, Gerald Choon Huat
Abstract : Objective: The increasing chronic disease burden has placed tremendous strain on tertiary healthcare resources in most countries, necessitating a shift in chronic disease management from tertiary to primary care providers. The Primary Care Network (PCN) policy was promulgated as a model of care to organise private general practitioners (GPs) into groups to provide GPs with resources to anchor patients with chronic conditions with them in the community. As PCN is still in its embryonic stages, there is a void in research regarding its ability to empower GPs to manage patients with chronic conditions effectively. This qualitative study aims to explore the facilitators and barriers for the management of patients with chronic conditions by GPs enrolled in PCN. Design: We conducted 30 semistructured interviews with GPs enrolled in a PCN followed by a thematic analysis of audio transcripts until data saturation was achieved. Setting: Singapore. Results: Our results suggest that PCNs facilitated GPs to more effectively manage patients through (1) provision of ancillary services such as diabetic foot screening, diabetic retinal photography and nurse counselling to permit a 'one-stop-shop', (2) systematic monitoring of process and clinical outcome indicators through a chronic disease registry (CDR) to promote accountability for patients' health outcomes and (3) funding streams for PCNs to hire additional manpower to oversee operations and to reimburse GPs for extended consultations. Barriers include high administrative load in maintaining the CDR due to the lack of a smart electronic clinic management system and financial gradient faced by patients seeking services from private GPs which incur higher out-of-pocket expenses than public primary healthcare institutions. Conclusion: PCNs demonstrate great promise in empowering enrolled GPs to manage patients with chronic conditions. However, barriers will need to be addressed to ensure the viability of PCNs in managing more patients in the face of an ageing population.